PENGARUH MEDIA TANAM PADA PERTUMBUHAN DAN KUALITAS MICROGREEN SAWI DAN SELADA - Adrialin, Gian; Suminar, Ratna (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
The need for nutrients for the body continues to increase, while the fulfillment of these nutrients is very limited. Through vegetables, fulfilling nutrients for the body, namely vitamins and fiber. However, currently the problem faced regarding vegetable production is limited space for vegetable cultivation. This is due to many factors, one of which is the conversion of agricultural land. Microgreen is an alternative that can be applied to overcome this problem. Microgreens are young plants that are rich in fiber and vitamins and are very good for fulfilling the body's nutrition. The focus of the research is to study how the planting medium affects the growth and quality of microgreens in mustard and lettuce plants. This study was conducted in Jambewangi from August to November 2024, using a completely randomized design , it involves 2 factors, each with 3 replications: planting medium (charcoal husk, cocopeat, malang sand, rockwool) and type of vegetables (mustard greens and lettuce). The results of the study showed that there was a real interaction between the type of vegetables and the planting medium on the fresh weight of plants in aged 11 HST, with the best results on husk charcoal x mustard greens, and the interaction between the type of vegetable and the planting medium also had a significant effect on the germination of rockwool x lettuce. The highest protein content was found in the cocopeat x lettuce treatment interaction (16.80%), while the total chlorophyll was the highest, namely 6.12 µmolm-2.